Arduino based soil moisture analyzer as an effective way for irrigation scheduling - Sayanthan, S.; Thiruvaran, T.; Kannan, N. (IEEE, 2018)
Through the present study we vindicated the crop water requirement for eggplant by using Arduino based soil moisture investigator and compared the total water requirement with the quantity of water being applied by farmers to save such excess quantity of water being wasted by the farmers. Therefore a device was established in the Arduino platform in order to detect the soil moisture, as the moisture sensor shows only the resistance between the two probes. It was calibrated with direct moisture meter to obtain the moisture readings directly. Then selected egg plants were planted in two drip fixed fields in two different times. Such time variation in planting was maintained to facilitate the root study in one field before the irrigation of the test field. Hence, according to the measured root length the soil moisture sensors were inserted into the soil in the test field and plants were irrigated up to the field capacity by using the moisture detection. The measured quantity of water which is actually needed by an eggplant up to 108 days after planting was around 149.26 liter. Simultaneously an investigation was carried out to find the quantity of water being applied by farmers. Finally. The measured quantity of water being applied by the farmers was 604.8 liter and it is 4.05 times higher than actual water requirement. Therefore, by using this soil moisture sensing technique it is possible to save a huge amount of water.
Keywords: Process control; Crop water requirement; Eggplant